Chemopreventive Effects of Curcumin Against 7,12-Dimethylbenz[a]anthracene-Induced Hamster Buccal Pouch Carcinogenesis - Maher Al-assaf; Nabil Kochaji; Shaza Al laham; Issa Al-Assaf; Caroline Mousallam; Charif Barakat (University Library System, University of Pittsburgh, 2024)
BACKGROUND: Chemoprevention is an important means that has a high potential to reverse, prevent or suppress the development of cancer in initial stages or the development of pre-cancerous cells to the cancer stage. OBJECTIVE: This study aimed to investigate the potential protective effect of curcumin as a chemopreventive agent against induced oral squamous cell carcinoma in Syrian hamster. MATERIALS AND METHODS: In this experimental study, forty male Syrian hamsters were divided equally into two main groups. The carcinogenic DMBA was only applied to the control group (g1 = 20 hamsters) by topical painting in the buccal pouch, as for the experimental group (g2 = 20 hamsters) curcumin was administered orally (80 mg\kg) concurrently with the DMBA. The animals were sacrificed at consecutive periods (after 2, 6, 10 and 14 weeks), then the histopathological changes in the buccal pouches were studied by H&E staining, and the VEGF expression during the previous sacrifice periods was studied. The Kruskal-Wallis test was used to study the significance of differences in VEGF expression between the two groups at the level of confidence 95%. RESULTS: P-value = 0.116>0.05 - 0.005<0.05 - 0.007<0.05 - 0.006<0.05, in 2, 6, 10 and 14 weeks respectively. Thus, the statistically significant differences in VEGF expression were found in the second, third and fourth sacrifice period between group 1 and group 2. CONCLUSION: Curcumin had chemopreventive effects against DMBA-induced buccal pouch OSCC through the modulating effect on the abnormal expression of VEGF.